Case‐control study of cumulative cigarette tar exposure and lung and upper aerodigestive tract cancers. Issue 9 (22nd February 2017) - Meyers, Travis J.; Chang, Shen‐Chih; Chang, Po‐Yin; Morgenstern, Hal; Tashkin, Donald P.; Rao, Jian‐Yu; Cozen, Wendy; Mack, Thomas M.; Zhang, Zuo‐Feng
Abstract : The development of comprehensive measures for tobacco exposure is crucial to specify effects on disease and inform public health policy. In this population‐based case‐control study, we evaluated the associations between cumulative lifetime cigarette tar exposure and cancers of the lung and upper aerodigestive tract (UADT). The study included 611 incident cases of lung cancer; 601 cases of UADT cancers (oropharyngeal, laryngeal and esophageal cancers); and 1, 040 cancer‐free controls. We estimated lifetime exposure to cigarette tar based on tar concentrations abstracted from government cigarette records and self‐reported smoking histories derived from a standardized questionnaire. We analyzed the associations for cumulative tar exposure with lung and UADT cancer, overall and according to histological subtype. Cumulative tar exposure was highly correlated with pack‐years among ever smoking controls (Pearson coefficient = 0.90). The adjusted odds ratio (95% confidence limits) for the estimated effect of about 1 kg increase in tar exposure (approximately the interquartile range in all controls) was 1.61 (1.50, 1.73) for lung cancer and 1.21 (1.13, 1.29) for UADT cancers. In general, tar exposure was more highly associated with small, squamous and large cell lung cancer than adenocarcinoma. With additional adjustment for pack‐years, positive associations between tar and lung cancer were evident, particularly for small cell and large cell subtypes. Therefore, incorporating the composition of tobacco carcinogens in lifetime smoking exposure may improve lung cancer risk estimation. This study does not support the claim of a null or inverse association between "low exposure" to tobacco smoke and risk of these cancer types. Abstract : What's new? Tobacco use is the leading preventable risk factor for cancer mortality worldwide, but emission differences between individual tobacco products are often not taken into account in exposure estimates. Here, the authors focused on this and estimated cumulative cigarette tar exposure from 39 government reports for participants of a case‐control study. This cumulative tar exposure was associated with lung cancer –especially small and large cell subtypes—even after adjusting for pack‐years. The data highlight the need to incorporate the composition of tobacco carcinogens in lifetime smoking exposure to improve lung cancer risk estimation.